Impact of discontinuing contact precautions and enforcement of basic hygiene measures on nosocomial vancomycin-resistant Enterococcus faecium transmission. (March 2022) - Eichel, V.M.; Boutin, S.; Frank, U.; Weigand, M.A.; Heininger, A.; Mutters, N.T.; Büchler, M.W.; Heeg, K.; Nurjadi, D.
Summary: Objectives: Vancomycin-resistant Enterococcus faecium (VREfm) has emerged as a pathogen of major concern for public health. Although definitive evidence is lacking, contact precautions have been a crucial element in infection prevention and control (IPC) strategies designed to limit nosocomial VRE transmission. This study investigated the effect of discontinuing contact precautions while enforcing basic hygiene measures, including hand hygiene, environmental cleaning and antiseptic body washing, for patients with VRE in intensive care units (ICUs) on the prevention of nosocomial VRE transmission causing bacteraemia. Methods: Contact precautions were discontinued in January 2018. In total, 96 VREfm isolates from 61 patients with VREfm bacteraemia and/or colonization hospitalized in eight ICUs in a tertiary care hospital in 2016 and 2019 in were characterized by whole-genome sequencing. VRE transmission was investigated using patient movement data and admission screening for reliable identification of nosocomial acquisition. Results: Discontinuation of contact precautions did not increase VREfm transmission events (eight in 2016 vs one in 2019). While the rate of endogenous VREfm was similar in both years (38% vs 31%), the number of non-colonized patients prior to VREfm bacteraemia was 16 (16/29, 55%) in 2019, which was significantly higher than in 2016 (8/32, 25%). The mean incidence density for VREfm bacteraemia was similar for both years (0.26 vs 0.31 per 1000 patient-days in 2016 and 2019, respectively). Conclusion: Discontinuation of contact precautions while enforcing basic hygiene measures did not lead to an increase in nosocomial bloodstream infection rates due to VREfm transmission in a hyperendemic ICU setting.